A Study of Drift Force on Submerged Body in X4-AUV Development - Safwan, Mohd Rawi; Zainah, Md. Zain (2014)
Autonomous Underwater Vehicles (AUVs) arerobots able to perform tasks without human intervention (remote operators). Research and development of thisclass of vehicles are growing, due to the excellentcharacteristics of the AUVs to operate in differentsituations. Therefore, this study aims to analyze the driftforce over different geometric configurations of an AUVhull, in order to reduce the drag force on the body. It isimportant to design an AUV with minimizing the dragforces acting on the hull to make AUV cruising smoothly. We also simulate the drift force for our X4-AUVellipsoidal shape to compare the results with other hullshape.